Membrane rafts regulate sperm acrosome reaction via cAMP-dependent pathway in chickens (Gallus gallus domesticus). Issue 5 (18th May 2018) - Priyadarshana, Chathura; Tajima, Atsushi; Ishikawa, Naoto; Asano, Atsushi
Abstract: Both transcriptionally and translationally inactive sperm need preassembled pathways into specific cellular compartments to function. Although initiation of the acrosome reaction (AR) involves several signaling pathways including protein kinase A (PKA) activation, how these are regulated remains poorly understood in avian sperm. Membrane rafts are specific membrane regions enriched in sterols and functional proteins and play important roles in diverse cellular processes, including signal transduction. Our recent studies on chicken sperm demonstrated that membrane rafts exist and play a role in multistage fertilization. These, combined with the functional importance of membrane rafts in mammalian sperm AR, prompted us to investigate the roles of membrane rafts in signaling pathways leading to AR in chicken sperm. Using 2-hydroxypropyl-β-cyclodextrin (2-OHCD), we found that the disruption of membrane rafts inhibits PKA activity and AR without affecting protein tyrosine phosphorylation; however, these inhibitions were abolished in the presence of a cyclic 3, 5-adenosine monophosphate (cAMP) analog. In addition, biochemical experiments showed a decrease in cAMP content in 2-OHCD-treated sperm, suggesting the involvement of soluble adenylyl cyclase (sAC) and transmembrane adenylyl cyclase (tmAC). Pharmacological experiments, combined with transcriptome analysis, showed that sAC and tmAC are present and involved in AR induction in chicken sperm. Furthermore, stimulation of both isoforms reversed the inhibition of PKA activity and AR in 2-OHCD-treated sperm. In conclusion, our results demonstrated that membrane rafts play an important role in AR induction by regulating the cAMP-dependent pathway and that they provide a mechanistic insight into membrane regulation of AR and sperm function in birds. Abstract : Membrane rafts regulate cAMP-dependent pathway via potentiating sAC and tmAC activities in chicken sperm, which enable them to enhance acrosomal responsiveness.